2014
DOI: 10.1371/journal.pone.0109537
|View full text |Cite|
|
Sign up to set email alerts
|

Remembering the Object You Fear: Brain Potentials during Recognition of Spiders in Spider-Fearful Individuals

Abstract: In the present study we investigated long-term memory for unpleasant, neutral and spider pictures in 15 spider-fearful and 15 non-fearful control individuals using behavioral and electrophysiological measures. During the initial (incidental) encoding, pictures were passively viewed in three separate blocks and were subsequently rated for valence and arousal. A recognition memory task was performed one week later in which old and new unpleasant, neutral and spider pictures were presented. Replicating previous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
(95 reference statements)
1
6
0
Order By: Relevance
“…Most likely, informative cues already triggered an emotion allowing participants to anticipate what they would experience in response to the target. This possibility accords with existing evidence on cued affective responding (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014) and on the relation between LPP amplitude and emotion (Yang et al, 2012; Herbert et al, 2013; Langeslag and van Strien, 2013; Sarlo et al, 2013; Galli et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most likely, informative cues already triggered an emotion allowing participants to anticipate what they would experience in response to the target. This possibility accords with existing evidence on cued affective responding (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014) and on the relation between LPP amplitude and emotion (Yang et al, 2012; Herbert et al, 2013; Langeslag and van Strien, 2013; Sarlo et al, 2013; Galli et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
“…Correspondingly, ERP studies found that affectively informative cues increase the LPP if they predict an emotional as compared to a neutral stimulus (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014). For example, in a study by Michalowski et al (2015), a colored fixation cross informed participants whether an upcoming picture would be neutral, unpleasant, or contained a spider.…”
Section: Introductionmentioning
confidence: 96%
“…Patients with post‐traumatic stress disorder (PTSD) exhibit attenuated P50 suppression to double‐click stimuli (reflecting sensory gating impairment) and exaggerated auditory and visual ERPs to simple, neutral stimuli (e.g., a tone), reflecting sensory cortical hyperactivity (Javanbakht, Liberzon, Amirsadri, Gjini, & Boutros, ; Lewine et al, ; Morgan & Grillon, ; Neylan et al, ; Skinner et al, ). Spider phobics demonstrate comparable exaggeration of visual ERPs (P1 and C1) to images of spiders and unrelated objects (Michalowski et al, ; Michalowski, Pane‐Farre, Low, & Hamm, ; Michalowski, Weymar, & Hamm, ). Of particular relevance here, besides aforementioned evidence of specific P1 enhancement to threatening faces, there is almost equally strong evidence of generic P1 enhancement to faces, regardless of facial expressions, in social anxiety (Helfinstein, White, Bar‐Haim, & Fox, ; Kolassa et al, ; Kolassa, Kolassa, Musial, & Miltner, ; Kolassa & Miltner, ; Muhlberger et al, ; Peschard, Philippot, Joassin, & Rossignol, ; Rossignol, Campanella, et al, ; Rossignol, Philippot, Bissot, Rigoulot, & Campanella, ; Wieser & Moscovitch, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with posttraumatic stress disorder (PTSD) exhibit attenuated P50 suppression to double-click stimuli (reflecting sensory gating impairment) and exaggerated auditory and visual ERPs to simple, neutral stimuli (e.g., a tone); reflecting sensory cortical hyperactivity (Javanbakht, Liberzon, Amirsadri, Gjini, & Boutros, 2011;Lewine et al, 2002;Morgan & Grillon, 1999;Neylan et al, 1999;Skinner et al, 1999). Spider phobics demonstrate comparable exaggeration of visual ERPs (P1 and C1) to images of spiders and unrelated objects (Michalowski et al, 2009;Michalowski, Pane-Farre, Low, & Hamm, 2015;Michalowski, Weymar, & Hamm, 2014). Of particular relevance here, besides aforementioned evidence of specific P1 enhancement to threatening faces, there is almost equally strong evidence of generic P1 enhancement to faces, regardless of facial expressions, in social anxiety (Helfinstein, White, Bar-Haim, & Fox, 2008;Kolassa et al, 2009;Kolassa, Kolassa, Musial, & Miltner, 2007;Kolassa & Miltner, 2006;Muhlberger et al, 2009;Peschard, Philippot, Joassin, & Rossignol, 2013;Rossignol, Philippot, Bissot, Rigoulot, & Campanella, 2012;Wieser & Moscovitch, 2015).…”
Section: Discussionmentioning
confidence: 99%